Nonsurgical management of mesenchymal hamartomas of the chest wall - Mila Kolar; Mercedes Pilkington; Mariana Silva; Donald Soboleski (Elsevier, 2018)
Background: Mesenchymal hamartomas of the chest wall (MHCW) are extremely rare extrapleural benign tumors. There is increasing utilization of nonoperative management given increased understanding of its benign biological behavior. Methods: A review of cases utilizing nonoperative management was completed. We present a case of complete spontaneous resolution of a MHCW managed nonoperatively with radiologic surveillance for five years. Results: Most reported cases were single case reports, with a total of 12 cases including our patient. From the reported cases on nonsurgical management eight were unilateral (67%), and four bilateral (33%). Two patients with unilateral involvement had multifocal lesions (29%). The majority of unilateral lesions were on the right side (85%). Three patients (27%) underwent subsequent surgical management after an initial period of conservative management. Two of these had bilateral involvement and the lesion was resected on only one side, while the third patient had unilateral multifocal involvement and underwent surgery for the predominant lesion only. Conclusion: Mesenchymal hamartomas of the chest wall are extremely rare extrapleural benign tumors. There is increasing utilization of nonoperative management given increased understanding of its benign biological behavior. We present a case of complete spontaneous resolution of a MHCW managed nonoperatively with radiologic surveillance for five years. Keywords: Mesenchymal hamartoma of the chest wall, Nonoperative, Children